Withdrawal strength and physical properties of three layers hybrid particleboard / Mohd Hanafi Umar - Umar, Mohd Hanafi (2012)
The objectives of this research were to evaluate the nail and screw withdrawal strength and the physical properties of the three-layer hybrid particleboard from Acacia mangium particles and wood sawdust in radial directions. 108 samples were produced in different density panels (500, 600 and 700kg/m3) and different resin contents (8:10:8 & 12:10:12) using Urea Formaldehyde (UF) resin. Based on the results of this study, it was found that when the densities were increased, the nail and screw withdrawal strengths were increased. When the resin content was increased, the nail and screw withdrawal strengths were also increased. The screw withdrawal strength was higher than the nail withdrawal strength. In the physical properties, the thickness and water absorption rates were increased when the densities and resin contents increased.